Exclusion of COL2A1 as a candidate gene in a family with Wagner-Stickler syndrome. Issue 2 (February 1990) - Fryer, A E; Upadhyaya, M; Littler, M; Bacon, P; Watkins, D; Tsipouras, P; Harper, P S
Abstract : A large family with Wagner's vitreoretinal degeneration but none of the non-ocular features of Stickler's syndrome has been studied with gene probes for type II collagen. Recombination has been observed, thus excluding type II collagen as the site of mutation in this family. This report supports other published evidence that the Wagner-Stickler syndrome is genetically heterogeneous.